EKSPLOITASI CUMI-CUMI DI PERAIRAN SELATAN PULAU AMBON - Welem Waileruny; Ketswin Pattirousamal; Delly D P Matrutty; Anthonius Sakliresi (Pattimura Proceeding, 2022)
Exploitation of squid by fisher’s on the southern coast of Ambon Island uses simple fishing technology with modifications based on fisher's experience. This study aims to describe tools and fishing methods, fishing seasons and areas, as well as analysis of production and income of squid fishing in the southern waters of Ambon Island. Data was collected through experimental fishing for 21 trips for each fishing gear and analysis was carried out descriptively and analysis of costs and income. The results showed that the use of a scoop net is one of the fishing gear that is not found elsewhere, while the jigger used has been modified by using underwater lights. Fishing areas in coastal areas with a distance of about 1 nautical mile. Data collection was carried out during the fishing season in September-December. Scoop net productivity is 49.5 kg/trip, and labor productivity is 16.5 kg/person/trip. Jigger production is 509.88 kg and labor productivity is 24.28 kg/person/trip. The net profit of each fisher’s per month from scoop and jigger are Rp.3,025,250 and Rp.2,665,000, respectively